2018
DOI: 10.1371/journal.pone.0192656
|View full text |Cite
|
Sign up to set email alerts
|

Lack of usefulness of computed tomography for surveillance in patients with aggressive non-Hodgkin lymphoma

Abstract: Surveillance computed tomography (CT) is usual practice for patients with aggressive non-Hodgkin lymphoma (aNHL) in complete remission (CR). However, evidence to support this strategy is lacking. We retrospectively analyzed our institutional lymphoma registry, including patients with lymphoma consecutively enrolled from June 1995 to October 2016. Of 1,385 patients with aNHL, 664 achieved CR and were followed up with or without surveillance CT. Surveillance CT was performed for 609 patients every 3 or 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Nevertheless, since most DLBCL patients achieved a sustained CMR, our cohort did not provide us enough relapsed patients to perform a subgroup analysis from time of relapse. However, some observational studies have already addressed the impact of detection by surveillance CT scan on survival, obtaining no differences between symptomatic and asymptomatic patients detected by routine CT scan [13][14][15]. Consequently, there are no data to clearly support routine imaging in asymptomatic DLBCL after first-line therapy, and especially in the PET-era.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, since most DLBCL patients achieved a sustained CMR, our cohort did not provide us enough relapsed patients to perform a subgroup analysis from time of relapse. However, some observational studies have already addressed the impact of detection by surveillance CT scan on survival, obtaining no differences between symptomatic and asymptomatic patients detected by routine CT scan [13][14][15]. Consequently, there are no data to clearly support routine imaging in asymptomatic DLBCL after first-line therapy, and especially in the PET-era.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination and blood tests, including serum lactate dehydrogenase (LDH), are recommended, along with clinical judgment [10]. Routine CT scans during follow-up have been assessed in several observational studies, with the rationale that early detection of lymphoma relapse might have a favorable impact on survival [11][12][13][14][15]. However, these retrospective studies have failed to show significant differences in survival derived from routine surveillance CT scans [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies of patients with curable lymphoma subtypes, such as diffuse large B-cell lymphoma (DLBCL) and Hodgkin lymphoma (HL), have reported that routine surveillance imaging with CT or positron emission tomography (PET) detects relapse in only few cases; most relapse cases are detected clinically, based on patient-reported symptoms, abnormal physical findings, and blood workup abnormalities. 1 10 Moreover, most previous studies have revealed that surveillance imaging offers no survival benefit for patients with curable lymphoma subtypes, mainly DLBCL and HL. 2 , 5 7 , 10 , 11 Given the excessive radiation exposure, medical costs, and unclear survival benefit associated with surveillance imaging, the 2014 Lugano classification discouraged its use for curable lymphoma subtypes, and the American Society of Hematology Choosing Wisely Campaign recommended limiting the use of surveillance CT for curable non-Hodgkin lymphoma (NHL).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Moreover, most previous studies have revealed that surveillance imaging offers no survival benefit for patients with curable lymphoma subtypes, mainly DLBCL and HL. 2,[5][6][7]10,11 Given the excessive radiation exposure, medical costs, and unclear survival benefit associated with surveillance imaging, the 2014 Lugano classification discouraged its use for curable lymphoma subtypes, and the American Society of Hematology Choosing Wisely Campaign recommended limiting the use of surveillance CT for curable non-Hodgkin lymphoma (NHL). 12,13 Follicular lymphoma (FL) is the second commonest subtype of NHL, accounting for 7-20% of NHL cases.…”
Section: Introductionmentioning
confidence: 99%